Caloric vestibular stimulation in aphasic syndrome - Wilkinson, David; Morris, Rachael; Milberg, William; Sakel, Mohamed (Frontiers in Integrative Neuroscience, 2013)
Caloric vestibular stimulation (CVS) is commonly used to diagnose brainstem disorder but its therapeutic application is much less established. Based on the finding that CVS increases blood flow to brain structures associated with language and communication, we assessed whether the procedure has potential to relieve symptoms of post-stroke aphasia. Three participants, each presenting with chronic, unilateral lesions to the left hemisphere, were administered daily CVS for 4 consecutive weeks. Relative to their pre-treatment baseline scores, two of the three participants showed significant improvement on both picture and responsive naming at immediate and one-week follow-up. One of these participants also showed improved sentence repetition, and another showed improved auditory word discrimination. No adverse reactions were reported. These data provide the first, albeit tentative, evidence that CVS may relieve expressive and receptive symptoms of aphasia. A larger, sham-controlled study is now needed to further assess efficacy.